2006
DOI: 10.1080/09583150500532014
|View full text |Cite
|
Sign up to set email alerts
|

Chondrostereum purpureumandFusarium tumidumindependently reduce regrowth in gorse (Ulex europaeus)

Abstract: An experiment was conducted in two gorse populations (Ulex europaeus ) in which Chondrostereum purpureum was applied each month as mycelial-agar cultures to the wounds of decapitated stems of previously untreated gorse plants to determine its potential as a mycoherbicide. Summer Á/autumn (Feb Á/May) or late winter Á/early spring (Aug Á/Sept) applications were effective in both populations, halving stem stump survival (from an average of 56 to 29%). Another experiment in the same gorse populations evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Further studies examining soil and juvenile application found that such applications caused significant reductions in seedling emergence and 95% mortality in juvenile plants [64,65]. The pathogen C. purpureum causes ‘silver leaf’ disease and has been suspected to be the cause of localised declines in woody weeds [66,67], albeit that its specific mode of action as a mycoherbicide is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies examining soil and juvenile application found that such applications caused significant reductions in seedling emergence and 95% mortality in juvenile plants [64,65]. The pathogen C. purpureum causes ‘silver leaf’ disease and has been suspected to be the cause of localised declines in woody weeds [66,67], albeit that its specific mode of action as a mycoherbicide is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…It has proven difficult to formulate Fusarium tumidum Sherb. in a way that produces consistent damage to gorse foliage, but Bourdôt et al (2006)…”
Section: Bioherbicides For Gorse Managementmentioning
confidence: 99%
“…This fungus is a widespread wound pathogen, commonly known as silver leaf disease, and is a plurivorous horticultural disease of economic importance. However, its broad host range has enabled successful mycoherbicide development against woody weeds in North America, South Africa and Europe, as well as against gorse in New Zealand (Bourdôt et al 2006). The use of C. purpureum for inundative biocontrol of Japanese honeysuckle may be limited, as its pathogenicity is restricted to woody tissues and therefore ineffective against rapid invasion by the herbaceous vines.…”
Section: Discussionmentioning
confidence: 99%